PENGARUH MODEL FLIPPED CLASSROOM DAN STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR KOMPUTER AKUNTANSI - Ambar Sari; siswandari siswandari; Asri Diah Susanti (Universitas Sebelas Maret, 2020)
Abstract This research aims to investigate: (1) the effect of flipped classroom model on student learning outcomes of accounting computer, (2) the effect of STAD model on student learning outcomes of accounting computer, and (3) the differences effect between the flipped classroom and STAD models on student learning outcomes of accounting computer. This type of research was a quasi experimenta design. The population of this research were the class XI of Accounting at a Vocational High School amounting to 105 students. The sample was the class XI of Accounting 2 and 3 with a purposive sampling technique. Data obtained from a cognitive, psychomotor, and an observed affective learning outcomes then analyzed using t-test. The conclusion of research show: (1) there is significant effect of flipped classroom model to student learning outcomes of accounting computer, with sig.0.000<0.05, (2) there is significant effect of STAD model to student learning outcomes of accounting computer, with sig.0.000<0.05, and (3) there is a significant difference effect between the flipped classroom and STAD models of students cognitive and psychomotor learning outcomes of accounting computer, with sig.<0.05, but there is no difference effect between the flipped classroom and STAD models of students affective learning outcomes of accounting computer. Keywords: Flipped Classroom, Student Team Achievement Division (STAD), Learning Outcomes, Accounting Computer AbstrakPenelitian ini bertujuan untuk menguji: (1) pengaruh model flipped classroom terhadap hasil belajar komputer akuntansi, (2) pengaruh model STAD terhadap hasil belajar komputer akuntansi, dan (3) perbedaan pengaruh antara model flipped classroom dan model STAD terhadap hasil belajar komputer akuntansi. Jenis penelitian ini adalah quasi experimental. Populasi penelitian ini adalah kelas XI Akuntansi SMK yang berjumlah 105 siswa. Sampel adalah kelas XI Akuntansi 2 dan 3 dengan teknik pengambilan sampel purposive sampling. Data yang diperoleh dari tes hasil belajar kognitif, unjuk kerja hasil belajar psikomotor, dan observasi hasil belajar afektif yang dianalisis menggunakan uji-t dengan SPSS. Hasil penelitian menyimpulkan: (1) ada pengaruh signifikan model flipped classroom terhadap hasil belajar komputer akuntansi, dengan sig.0.000<0.05, (2) ada pengaruh signifikan model STAD terhadap hasil belajar komputer akuntansi, dengan sig.0.000<0.05, dan (3) ada perbedaan signifikan pengaruh antara model flipped classroom dan model STAD terhadap hasil belajar kognitif dan psikomotor komputer akuntansi, dengan sig<0.05 tetapi tidak ada perbedaan pengaruh antara model flipped classroom dan model STAD terhadap hasil belajar afektif komputer akuntansi.Kata Kunci: Flipped Classroom, Student Team Achievement Division (STAD), Hasil Belajar, Komputer Akuntansi